(3GdeSFhhdjI GdLfGFjI dWHjH GdJNOjQ Yf GdCNWGA GdegfjI h GdeGOjI (B: s (3OQGSI ebGQfI (B/ s - (3eMehO eMeO GdSjO Gdabis; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JHMK gPg GdOQGSI CSGS eTQhYjI eeGQSI GdYed GdWHi (B: (3h GdNdGa Gdabgi Mhd GdeSFhdjI GdLfGFjI ddWHjH HUaI YGeI(B: (3Ke JHjf eOi GSJbdGdjI GdeSFhdjI GdLfGFjI dWHjH GdJNOjQ Yf GdeSFhdjI GdLfGFjI ddLQGM(B: (3Ke JfJbd dHMK GdeSFhdjI GdLfGFjI dWHjH GdJNOjQ Yf GdCNWGA GdegfjI ai GdeLGdGJ GdJbdjOjI (B((3LQGFe GdNWC GdWHi ZjQ GdYeOi(B) (3HjGf CQcGfgG GdKdGKI GdNWC h GdVQQ h GdSHHjI(B: (3Ke JfJbd dHMK GdeSFhdjI GdLfGFjI dWHjH GdJNOjQ Yf GdCNWGA GdegfjI ai GdeLGdGJ GdeSJMOKI dGSjeG ai ehVhY JMOjO dMXI GdhaGI h ehVhY GSJNOGe CLgRI GdGfYGT GdUfGYi h ehVhY fbd h RQY GdCYVGA GdHTQjI(B: (3h CNjQG JfJbd GdOQGSI dHMK GdeSFhdjI GdLfGFjI dWHjH GdJNOjQ Yf LQGFe EaTGA GdSQ GdWHi h GdELgGVs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2015s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B250-263s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdCNWGA GdegfjI h GdeGOjIs; (3GaTGA GdSQ GdWHjs; (3WHjH GdJNOjQs; (3eSGAdI GdWHjH LfGFjGs; (3GdNWC GdWHj ZjQ GdYeOis; (3fbd GdGYVGAs; (3GdVQQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs